The genus Cyamiocardium Soot-Ryen, 1951 (Bivalvia: Cyamiidae) in sub-Antarctic and Antarctic waters - Urcola, Matías R.; Zelaya, Diego Gabriel (Polar Biology)
For more than 50 years the genus Cyamiocardium was regarded as represented by three species: Cyamiocardium denticulatum (with Cyamiocardium rotundatum as a synonym), Cyamiocardium dahli, and Cyamiocardium crassilabrum. However, in the last years, the latter was removed from Cyamiocardium, alternatively being placed into Perrierina. All these species were mainly based on the general shell morphology of a reduced number of specimens, with scarce (or no) information on their anatomy and reproductive traits. The present study provides the first systematic revision of the species of Cyamiocardium occurring in sub-Antarctic and Antarctic waters. For that, an extant source of material was available; and several characters not studied (in detail) before, such as prodissoconch morphology and microsculpture, gross anatomy, and reproductive characteristics, were investigated. As part of this study, the identity of C. denticulatum (the type species of the genus) and that of C. dahli are clarified. In addition, C. rotundatum is revalidated as a full species, and C. crassilabrum is transferred again to Cyamiocardium. Furthermore, three new species were detected and are described herein: Cyamiocardium chuanisinense new species, Cyamiocardium namuncurense new species, and Cyamiocardium yeskumaala new species. The new information arising from this study is used to redefine the genus Cyamiocardium, and to re-analyze the similarities/differences of this genus with other cyamiids. Fil: Urcola, Matías R. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina Fil: Zelaya, Diego Gabriel. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina